Yield and quality of alfalfa (Medicago sativa L.) in response to fertilizer application in China: A meta-analysis - Wan, Weifan; Li, Yuejin; Li, Haigang (Frontiers in Plant Science, 2022)
Introduction In China, alfalfa (Medicago sativa L.) often grows in marginal land with poor soil fertility and suboptimal climate conditions. Alfalfa production cannot meet demands both in yield and quality. It is necessary to apply fertilizers to achieve high yields and produce high-quality alfalfa in China. However, there is no understanding on the impact of fertilizer application on alfalfa production and the possible optimal application rates across China. Methods We conducted a meta-analysis to explore the contribution of fertilizer application to the yield and quality of alfalfa based on a dataset from 86 studies published between 2004 and 2022. Results and Discussion The results showed that fertilizer application not only increased alfalfa yield by 19.2% but also improved alfalfa quality by increasing crude protein (CP) by 7.7% and decreasing acid detergent fibre by 2.9% and neutral detergent fibre by 1.8% overall compared to the non-fertilizer control levels. The combined nitrogen (N), phosphorus (P) and potassium (K) and combined NP fertilizer applications achieved the greatest yield and CP concentration increases of 27.0% and 13.5%, respectively. Considering both yield and quality, the optimal rate of fertilizer application ranged from 30 to 60 kg ha-1 for N, 120 to 150 kg ha-1 for P and less than 120 kg ha-1 for K. Meta-analysis further showed that the effect of fertilizer application on yield was greater in low soil organic matter (SOM) soils than in high SOM soils. In conclusion, fertilizer application is an effective strategy to improve the yield and quality of alfalfa in China, especially that grown in low SOM soils. This study is helpful for optimizing fertilization schedules of alfalfa in China.